Lesions of the jaws presenting as radiolucencies on cone-beam CT. Issue 10 (October 2016) - MacDonald, D.
Abstract : In order to compliment the current interest in lesions affecting the face and jaws in Clinical Radiology, this overview addresses recent developments in the classification, nomenclature, clinical and radiological diagnosis, and outcomes of treatment of the most important and frequent lesions that present as radiolucencies on conventional radiography of the jaws. Although termed "benign" a significant proportion of each odontogenic neoplasm can recur after conservative surgery. Two diagnostic flowcharts take the clinician from the radiological presentation of a lesion in the jaw to an appropriate diagnosis. The recent advent of cone-beam computed tomography (CBCT) can enhance the quality of the diagnosis and preoperative assessment of such lesions. CBCT images of typical benign neoplasms, cysts, and other phenomena affecting the face and jaws are included. The relative period prevalences of the lesions, based on the most recent UK reports, are included. The importance to the radiologist of an emerging lesion of the jaws, the glandular odontogenic cyst, is discussed.